DESIGN OF A MECHANICAL SYSTEM FOR A DRONE DELIVERY PACKAGE WITH A CAPACITY OF 2-3 KG - Nofri Chailillul Rahmad Ihsan; Desmarita Leni; Muchlisinalahuddin Muchlisinalahuddin; Yuni Vadila; Muhammad Subri (Yayasan Education and Social Center, 2026)
The increasing need for fast delivery drives the development of drones as an alternative logistics solution. However, increasing payload capacity impacts thrust requirements, power consumption, and structural stability, necessitating integrated mechanical design. This study aims to design a mechanical system for a 2-3 kg package delivery drone with a stable and energy-efficient quadcopter configuration at maximum payload conditions. The method used is a design engineering approach through 3D CAD modeling, mass distribution and center of gravity (CoG) analysis, and thrust and power estimation using momentum theory. Evaluations were carried out on the total system weight, hover thrust requirements, hover power, and peak power with a thrust-to-weight (T/W) ratio of 1.8-2.0. The results show that at a total mass of ±6.5 kg, a minimum thrust of approximately 1.63 kgf per motor is required for stable hovering. The estimated hover power is around 1.04 kW, while the peak power is close to 3 kW. The 6S 15,000 mAh battery configuration is capable of providing a hover duration of approximately 15 minutes. This design demonstrates technical feasibility for medium-scale logistics drone applications.